Cancer-associated fibroblasts and their prognostic role in colorectal cancer: review and meta-analysis - Ilie, Silvia Mihaela; Gales, Laurentia; Musina, Ana Maria; Rouet, Kevin; Stefan, Alexandra Elena; Belceanu, Mara Simona; Trandafir, Anda Stefania; Guillaume, Constantin; Bertaut, Aurélie; Charifi, Ikram; Cueff, Adel; Derangère, Valentin; et al. (Frontiers in Oncology, 2025)
BackgroundCancer-associated fibroblasts (CAFs) are a component of the tumor microenvironment, influencing tumor behavior and progression. This meta-analysis aims to describe the prognostic value of CAF biomarkers in colorectal cancer (CRC).MethodsA systematic search of the existing literature was performed in Medline and Embase on CAF immunohistochemical (IHC) biomarkers and their association with disease-free survival (DFS) and overall survival (OS). The selection of studies was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines and Population, Intervention, Comparator, Outcome criteria. The quality of the included articles was assessed using the Newcastle–Ottawa Scale.ResultsA total of 3,535 records were identified, of which 84 were selected for the qualitative review and 59 (N = 15,396 patients) were included in the final meta-analysis. In general, CAF biomarker expression was associated with poor prognosis, with high heterogeneity among studies. Significant results for DFS were found for cluster of differentiation (CD) 163, matrix metalloproteinase 9 (MMP-9), and tenascin C. The following markers were significantly associated with OS: CD163, MMP-9, periostin, and vimentin.ConclusionSeveral CAF IHC biomarkers, particularly CD163, MMP-9, periostin, and vimentin, significantly associated with prognosis in CRC, could be proposed as surrogates for the phenotypical characterization of the tumor microenvironment.